EP30 Understanding which patient-reported outcomes are important to rheumatology patients: findings from ArthritisPower. (20th April 2020) - Daud, Tariq; Nowell, William B; Kannowski, Carol L; Gavigan, Kelly; Cai, Zhihong; Cardoso, Anabela; Hunter, Theresa; Birt, Julie; Workman, Jennifer; Curtis, Jeffrey
Abstract: Background: Little is known about PRO measures patients find most important for disease, treatment effectiveness/health outcomes. In this study, we examined PROs selected by patients with rheumatologic conditions to further elucidate which disease symptoms they found most important to track within ArthritisPower registry. As the study is ongoing, we discuss initial PRO selections of study participants. Methods: Adult US patients with self-reported rheumatoid arthritis (RA), psoriatic arthritis (PsA), ankylosing spondylitis (AS), systemic lupus erythematosus (SLE), osteoporosis (OP), osteoarthritis (OA), fibromyalgia syndrome (FMS) in ArthritisPower were invited to participate and prompted to select up to ten PRO (symptom) measures they felt were important to track their condition at baseline via ArthritisPower smartphone and Web-based app. PROs Measurement Information System (PROMIS) instruments focusing on symptoms of pain, physical and cognitive function, mental health, fatigue, social function, work impact, sexual function, and sleep, and Outcomes Measures in Rheumatology (OMERACT) RA flare instrument (only for those with RA) and Lilly-developed morning joint-stiffness duration question were offered. At Month (m)1, m2, m3, participants were given the option to continue tracking their selected PRO measures or change. At m3, participants complete an exit survey prioritizing all measures selected during participation and specifying other symptoms not available they would have wanted to track. Descriptive statistics were conducted on baseline data. Results: As of May 2019, 292 participants enrolled (251 completed baseline assessments). Mean age was 55.6 (9.2) years, 89.6% female, 91.2% White, mean disease duration of 12 (10.7) years; similar to the overall ArthritisPower population. Majority (64.1%) self-reported OA, followed by RA (49.0%), FMS (40.6%), PsA (26.3%), OP (20.3%), AS (15.5%), SLE (5.6%), not mutually exclusive. Top 3 PRO domains chosen at baseline were fatigue, mental health, pain (Table 1 ). Average number of instruments selected for baseline completion was 6.9 (2.4). Conclusion: Participants prioritised tracking fatigue, aspects of mental health, pain, physical function, social function, sleep, morning stiffness. These findings provide insights into symptoms rheumatology patients find most important; useful to inform the design of future patient-centric clinical trials and real-world evidence generation. Disclosures: T. Daud (Non-Author Presenter) None. W.B. Nowell: Shareholder/stock ownership; WN has Ownership Interest (stocks, stock options, or other ownership interest excluding diversified mutual funds). C.L. Kannowski Corporate appointments; CLK is an employee of Eli Lilly and Company. Shareholder/stock ownership; CLK owns stock options at Eli Lilly and Company. K. Gavigan: None. Z. Cai: Corporate appointments; ZC is an employee of Eli Lilly and Company. Shareholder/stock ownership; shareholder of Eli Lilly and Company. A. Cardoso: Corporate appointments; AC is an employee of Eli Lilly and Company. Shareholder/stock ownership; AC is a stockholder of Eli Lilly and Company. T. Hunter: Corporate appointments; TH is an employee of Eli Lilly and Company. Shareholder/stock ownership; TH is a shareholder of Eli Lilly and Company. J. Birt: Corporate appointments; JB is an employee of Eli Lilly and Company. Shareholder/stock ownership; JB is a shareholder of Eli Lilly and Company. J. Workman: Corporate appointments; JW is an employee of Eli Lilly and Company. J. Curtis: Consultancies; JC has received Consulting Fees from AbbVie, Amgen, BMS, Corrona, Eli Lilly, Janssen, Myriad, Pfizer, Regeneron, Roche, UCB. Grants/research support; JC has received grants/research support from AbbVie, Amgen, BMS, Corrona, Eli Lilly, Janssen, Myriad, Pfizer, Regeneron, Roche, UCB.